2007
DOI: 10.3928/1081-597x-20070201-09
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Loss After Toric Iris-fixated Phakic Intraocular Lens Implantation: Three-year Follow-up

Abstract: PURPOSE: To study quantitative changes in endothelial cell count after implantation of the toric iris-fi xated phakic intraocular lens. METHODS: A prospective, non-randomized, self-controlled clinical trial was conducted of 40 eyes (28 myopic, 12 hyperopic) of 23 patients with high ametropia and astigmatism. Non-contact computer-assisted endothelial microscopy was performed before and 1, 2, and 3 years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…14 Also Tehrani and Dick reported that the annual cumulative endothelial cell loss was 1.9% for irisclaw lenses. 15 We had 6.85% and 6.63% endothelial cell loss in both groups 1 and 2, respectively, and an annual decline of 2.70% and 3.70%, respectively. None of eyes suffered a decrease of more than 15% of corneal endothelial cells or a rate of less than 1500 cells/mm 2 means which would require an IOL explantation in the end of 18 months.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…14 Also Tehrani and Dick reported that the annual cumulative endothelial cell loss was 1.9% for irisclaw lenses. 15 We had 6.85% and 6.63% endothelial cell loss in both groups 1 and 2, respectively, and an annual decline of 2.70% and 3.70%, respectively. None of eyes suffered a decrease of more than 15% of corneal endothelial cells or a rate of less than 1500 cells/mm 2 means which would require an IOL explantation in the end of 18 months.…”
Section: Discussionmentioning
confidence: 70%
“…reported that an initial 10.6% reduction in ECD was noted in the first year of angle‐supported lenses, followed by a mean annual decline rate of 1.78% 14 . Also Tehrani and Dick reported that the annual cumulative endothelial cell loss was 1.9% for iris‐claw lenses 15 . We had 6.85% and 6.63% endothelial cell loss in both groups 1 and 2, respectively, and an annual decline of 2.70% and 3.70%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In one study [8], the results of toric Artisan implantation were evaluated in myopic, hyperopic and mixed astigmatism and showed reduction of cylinder from 4.3 AE 0.7 to 1.4 AE 1.2 D in myopic astigmats, from 4.6 AE 0.8 to 0.9 AE 0.8 D in hyperopic astigmats, and from 4.4 AE 1.5 to 1.8 AE 2.3 D in the mixed astigmatism group with efficacy indices of 1.6, 1.3 and 1.3, respectively [8]. In evaluation of endothelial cell loss after toric Artisan at 3 years' follow-up, Tehrani and Dick [11 ] found an annual cumulative cell loss of À1.9% for the myopic group and À1.6% for the hyperopic group, which is two to three times greater than physiologic annual cell loss in normal eyes without surgery.…”
Section: Iris-fixed Phakic Intraocular Lensmentioning
confidence: 99%
“…Nonsurgical management of high levels of corneal astigmatism is often limited because topographic irregularities make contact lens fitting difficult and spectacles often cause intolerable levels of aniseikonia. Surgical management of high astigmatism includes corneal wedge resection, 1 relaxing incisions with or without compression sutures, 2-4 astigmatic keratotomy (AK), [5][6][7] photorefractive keratectomy (PRK), 8 laser in situ keratomileusis (LASIK), 9 intrastromal corneal ring segment implantation, 10 toric intraocular lens (IOL) implantation, [11][12][13] and conductive keratoplasty (CK). [14][15][16] Photorefractive keratectomy and LASIK produce less predictable results and are limited in the amount of astigmatism they can correct.…”
mentioning
confidence: 99%